Identification of Zingiberaceae as medicinal plants in Gunung Cut Village, Aceh Barat Daya, Indonesia - Zahara, Meutia; Hasanah, Mauizah; Zalianda, Rahma (Journal of Tropical Horticulture, 2018)
Zingiberaceae is well known as gingers family with abundant numbers of spices widely used in Southeast Asia, because of their unique flavors, ornamental and also the medicinal values. The extracts of Zingiberaceae rhizome contain many essentials oils, including terpenes, alcohols, ketones, flavonoids and phytoestrogens that use as medicine. Zingiberaceae grow vigorously in a wide range of habitats ranging from riverine to the limestone area, from lowland to the upper mountain regions. They often grow in shady area but some of the native species are able to tolerate to the sun exposure. The cultivation of this family was developed widely. Gunung Cut Village is one the villages in Aceh Barat Daya district which cultivated four species of this family: Zingiber officinale, Curcuma domestica, Alpina galanga and Kaempferia galanga. They mainly use for medicinal purposes as it can cure many diseases traditionally.